Occupational Health and Safety Perceptions of Healthcare Workers in Traditional and Complementary Medicine Practice Centers: A Cross-Sectional Study in Istanbul - Fatma Polat; Aybüke Günaltay; Ali Timucin Atayoglu (Karaelmas İş Sağlığı ve Güvenliği Dergisi, 2026)
This cross-sectional study investigated the knowledge, awareness, and consciousness levels regarding Occupational Health and Safety (OHS) among healthcare professionals in Traditional and Complementary Medicine (T&CM) Centers in Istanbul. A total of 52 participants from eight centers were surveyed between August 2024 and January 2025 using validated tools. The response rate was 86.7%. The participants showed high consciousness (92.0%), moderate awareness (80.0%), and lower knowledge (77.0%). The allied health professionals had significantly higher awareness than physicians and nurses (p = 0.003). The prior OHS training was reported by 96.2% of participants. A moderate positive correlation was found between awareness and knowledge (r = 0.533, p < 0.01). Although the awareness and consciousness levels were generally adequate, knowledge gaps persisted. The findings highlight the need for context-specific, evidence-based OHS training in T&CM settings to ensure safer workplaces and improve healthcare outcomes.